Thyroid function among women with gestational trophoblastic diseases: A cross-sectional study - Düğeroğlu, Harun (2019)
BACKGROUND: Gestational trophoblastic diseases (GTDs) are treatable rare tumors with wide distribution. The estimated incidence of GTDs varies dramatically between different regions globally. In early pregnancy, there may be high human chorionic gonadotropin (HCG) concentrations, normal or slightly increased free T4 (fT4) and subnormal thyroid-stimulating hormone (TSH), causing hyperthyroidism ranging from subclinical to severe. Beta-HCG causes thyrotoxicosis through thyroid stimulation in patients with trophoblastic tumors. OBJECTIVE: To assess thyroid function among patients diagnosed with complete or partial hydatidiform mole, within the GTD spectrum. DESIGN AND SETTING: Cross-sectional study based on patients’ medical records at Van University Hos-pital, Van, Turkey. METHODS: 50 patients monitored due to diagnoses of hydatidiform mole were included and were ex-amined regarding thyroid function. Thyroid gland size and volume were measured using thyroid ultraso-nography. Beta-HCG, TSH, fT4, free T3 (fT3), total T4 (TT4), total T3 (TT3), anti-thyroid peroxidase (anti-TPO), anti-thyroglobulin (anti-TG) and thyroglobulin levels were measured. RESULTS: Among these patients, 15 (30%) were diagnosed with complete hydatidiform mole and 35 (70%) with partial hydatidiform mole, according to pathology results. Those with complete hydatidiform mole were older (P = 0.003), with higher number of pregnancies (P = 0.032), lower TSH level (P = 0.011) and higher fT4 and TT4 levels (P = 0.04; P = 0.028), compared with partial hydatidiform mole patients. CONCLUSION: In hydatidiform mole patients, thyroid disease severity increases with age, parity, beta-HCG level and mole size. However, prospective multicenter studies on this topic are needed, with larger num-bers of patients and closer monitoring.